A non-selective (amitriptyline), but not a selective (citalopram), serotonin reuptake inhibitor is effective in the prophylactic treatment of chronic tension-type headache. Issue 3 (September 1996) - Bendtsen, L; Jensen, R; Olesen, J
Abstract : OBJECTIVES: Although the tricyclic antidepressant amitriptyline is extensively used in the prophylactic treatment of chronic tension-type headache, only few studies have investigated the efficacy of this treatment and the results are contradictory. In addition, the new selective serotonin reuptake inhibiting antidepressants, which are widely used in depression and of potential value in pain management, have never been investigated in a placebo controlled study of tension-type headache. The aim was to evaluate the efficacy of amitriptyline and of the selective serotonin reuptake inhibitor citalopram in chronic tension-type headache. METHODS: Forty non-depressed patients with chronic tension type headache were included in a 32 week, double blind, placebo controlled, three-way crossover study. RESULTS: Thirty four patients completed the trial. Amitriptyline reduced area under the headache curve by 30% compared with placebo (P = 0.002), whereas citalopram had no significant effect (P = 0.68). Explanatory analyses showed that amitriptyline significantly reduced the duration of headache (P = 0.01), headache frequency (P = 0.01), and intake of analgesics (P = 0.02) but not headache intensity (P = 0.12). CONCLUSION: Although amitriptyline did not eliminate the headache, it provided a clinically important reduction of headache in the majority of otherwise treatment resistant patients. The differential effect of amitriptyline and citalopram indicates that mechanisms other than inhibition of serotonin reuptake are involved in the analgesic effect of the tricyclic antidepressants. Amitriptyline, but not citalopram, is valuable in the prophylactic treatment of chronic tension type headache.